Are low income countries targets of the tobacco industry? Plenary lecture given during the Conference on Global Lung Health and 1997 Annual Meeting of the International Union Against Tuberculosis and Lung Disease, Palais des Congrès, Paris, France, 1-4 October 1997 - (:unkn) unknown (My University, 1999)
Estimations show that tobacco consumption is steadily increasing in low income countries already deprived of basic human needs, such as adequate food and water supplies and education. Among the many factors affecting this, the most significant is the aggressive marketing strategies of the tobacco industry. The tobacco industry operates by denying health evidence, sponsoring scientific research that diverts attention to other fields, investing heavily in promotion and advertising, interfering with national public health laws, forming joint ventures with national monopolies, and persuading governments on the risks of smuggling. Turkey, a tobacco-growing country, opened its markets to the multinational tobacco industry after 1984. This paper presents examples of the marketing strategies used by the tobacco industry in the last two decades, and shows the consequences for Turkey in the hope that this information can help other low income countries that are not yet targets of the invasion of the tobacco industry.
Keywords: Humans; Turkey; Developing Countries; Smoking; Health Education; Agriculture; Tobacco Industry; Income